El delito de conspiración para el tráfico ilícito de drogas: análisis del cuarto párrafo del artículo 296 del Código Penal - Valdez Pimentel, Fernando (2021)
The author analyzes what should be understood by the crime of conspiracy in a general framework, to later interpret conspiracy crimes according to criminal law, emphasizing the crime of conspiracy for drug trafficking. Likewise, he focuses his attention on answering whether it is dogmatically possible and constitutionally legitimate to apply the aggravating circumstances of article 297 to the fourth paragraph of article 296 of the Penal Code, concluding that it is not.